Psychobehavioural Factors Are More Strongly Associated with Successful Weight Management Than Predetermined Satiety Effect or Other Characteristics of Diet - Leila Karhunen; Marika Lyly; Anja Lapveteläinen; Marjukka Kolehmainen; David E. Laaksonen; Liisa Lähteenmäki; Kaisa Poutanen (Hindawi Limited, 2012)
This study aimed to investigate factors associated with weight management, especially whether satiety value of food as a part of a weight-maintenance diet would affect self-regulation of food intake and weight management. Altogether 82 obese subjects completed the study consisting of weight-loss and weight-maintenance (WM) periods. During the WM, subjects were randomized into higher- and lower-satiety food groups. No differences were observed in the changes in body weight, energy intake, or eating behaviour between the groups, even despite the different macronutrient compositions of the diets. However, when regarding all study subjects, success in WM was most strongly associated with a greater increase in the flexible control of eating and experience of greater easiness of WM and control of food intake and a greater decrease in uncontrollable eating and psychological distress. Psychobehavioural factors seem to be more strongly associated with successful weight management than the predetermined satiety effect or other characteristics of the diet.